GAMBARAN KELENGKAPAN DAN KESERAGAMAN PENULISAN ODONTOGRAM OLEH DOKTER GIGI DI KOTA SEMARANG - Moh. Yusuf; Syuhada Setiawan; Andina Rizkia Putri Kusuma (Faculty of Dentistry, Universitas Islam Sultan Agung, 2019)
Background: Odontogram is one part of the dental record. The odontogram form isfilled with diagnoses and treatment done by the dentist. Odontogram can be used for the further treatment plan and help the forensic department to do the identification. The purpose of this study was to identify the completeness of odontogram filling out by the dentist in Semarang.Method: The research was descriptive using a cross-sectional study design. The subject of the research was graduated dentist in year 2015 until 2017. Subjects were chosen through information from PDGI.Result: The result of this study showed that none of the subjects filled odontogramcompletely, 5 subjects filled less complete and 39 others were categorized incomplete according to medical record guidance book published in 2015.Conclusion: Based on the study, concluded that the need to pay attention aboutthe importance of filling odontogram by the dentist was still low.